Actin dynamics in silico, in waves, and in rods - Pak, Chi W., author; Bamburg, James, advisor (Colorado State University. Libraries, 2009)
The current paradigm of actin dynamics and superorganization has advanced in the past decade from emerging technologies and perspectives, which include the discovery of actin nucleators, real time imaging of the dynamics of single filaments in vitro, and single molecule imaging of actin superstructures in vivo. These advances have influenced each of our studies on multiple levels, sometimes directly. A novel analysis of single actin filament dynamics revealed faster than expected dynamics during treadmilling but not during bulk polymerization. Using an exact stochastic simulation, we investigated whether filament-annealing and -fragmentation might account for faster than expected dynamics; their influence on actin dynamics had not been investigated before in a comprehensive model. Results from our work demonstrated that filament-annealing and -fragmentation alone cannot account for faster than expected dynamics during treadmilling. Thus, strictly through computational modeling, we are able to investigate various hypothetical models and offer insights into a process that cannot be achieved by experimentation. A concept that has also gained support during the past decade has been the self-organizing nature of actin, which was demonstrated by the Listeria actin-comet-tail reconstitution assay. We have proposed that this is a fundamental property of all actin superstructures, whether they are assembled in vitro or in vivo or whether they are involved in development or disease. The concept of actin's self-organization has influenced our study of neuronal waves, which are growth cone-like structures that travel along neurites and which were hypothesized to transport actin to growth cones and support neuritogenesis. Using diffusional analysis, we were able to demonstrate that neuronal waves transport actin. Neuronal waves provide a unique mechanism for transporting actin in that the delivery of actin is dependent upon actin itself and its dynamics. In disease states, the self-organization of actin is often changed but not disrupted, sometimes resulting in the formation of orderly-structured aggregates of cofilin and actin known as cofilin-actin rods (or rods). Using glutamate excitotoxicity as a model system for the cofilin pathology observed in Alzheimer disease (AD), we have determined signaling mechanisms for cofilin-actin rod induction, which in young rat hippocampal neurons require AMPA receptors and are calcium-independent. In addition, cofilin-actin rod interactions with microtubule associated proteins, and associated changes to the microtubule cytoskeleton were studied for its potential relevance to the pathology of AD. Our results suggest that disruptions to the normal organization of actin and microtubules might underlie several pathological hallmarks of early AD.
Keywords: actin; cofilin; self-organization; molecular biology; neurosciences; cellular biology